Insulin Resistance of Normal Weight Central Obese Adolescents in Korea Stratified by Waist to Height Ratio: Results from the Korea National Health and Nutrition Examination Surveys 2008–2010 - Won Kyoung Cho; Hyojin Kim; Hyun Young Lee; Kyung Do Han; Yeon Jin Jeon; In Ah Jung; Shin Hee Kim; Kyoung Soon Cho; So Hyun Park; Min Ho Jung; Byung-Kyu Suh (International Journal of Endocrinology)
Background. To evaluate insulin resistance of normal weight central obese 13–18-year-old male and female adolescents stratified by waist to height ratio (WHR). Methods. Data were obtained from the Korea National Health and Nutrition Examination Survey (K-NHANES) conducted during 2008–2010. Central obesity was defined as that in the upper quartile of age and sex specific WHR. Subjects were classified into no central obesity normal weight (NW), central obesity normal weight (CONW), no central obesity overweight (OW), and central obesity overweight (COOW). Results. The prevalence of CONW was 9.6% (83/832) in female and 7.0% (61/909) in male. CONW showed higher levels of insulin (P<0.006), HOMA-IR (P<0.006), and ALT (P<0.001) than NW in female. CONW had higher levels of insulin (P<0.0001), HOMA-IR (P<0.0001), and WBC count (P<0.021) and lower level of HDL (P<0.0001) than NW in male. WHR and BMI had similar significant correlations with MS components. CONW showed 2.5 times (95% confidence interval, 1.21–5.00) more likelihood to have high insulin resistance than NW in male. Conclusions. Screening for central obesity using WHR in clinical setting is recommended.